Verify a – (– b) = a + b for the following values of a and b : a = 118, b = 125
Answers
Answered by
12
Question: Verify a – (– b) = a + b for the following values of a and b : a = 118, b = 125
Solution: To verify the above expression put the values of a and B in the expression,solve it then verify the expression.
LHS:
![a - ( - b) \\ \\ = 118 - ( - 125) \\ \\ = 118 + 125 \\ \\ = 243 \\ \\ a - ( - b) \\ \\ = 118 - ( - 125) \\ \\ = 118 + 125 \\ \\ = 243 \\ \\](https://tex.z-dn.net/?f=a+-+%28+-+b%29+%5C%5C+%5C%5C+++%3D+118+-+%28+-+125%29+%5C%5C++%5C%5C++%3D+118+%2B+125+%5C%5C++%5C%5C++%3D+243+%5C%5C++%5C%5C+)
RHS :
![a + b \\ \\ = 118 + 125 \\ \\ = 243 a + b \\ \\ = 118 + 125 \\ \\ = 243](https://tex.z-dn.net/?f=a+%2B+b+%5C%5C++%5C%5C++%3D+118+%2B+125+%5C%5C++%5C%5C++%3D+243)
thus LHS = RHS.
Solution: To verify the above expression put the values of a and B in the expression,solve it then verify the expression.
LHS:
RHS :
thus LHS = RHS.
Answered by
13
Given :
a - (- b) = a + b
we know, that ( - ) x ( - ) = ( + )
Given :
a = 118 and b = 125
substituting the values of "a" and "b "
a - (- b) = a + b
118 - (- 125) = 118 + 125
118 + 125 = 118 + 125
243 = 243
Hence : Values are same.
Verified : a - (- b) = a + b
a - (- b) = a + b
we know, that ( - ) x ( - ) = ( + )
Given :
a = 118 and b = 125
substituting the values of "a" and "b "
a - (- b) = a + b
118 - (- 125) = 118 + 125
118 + 125 = 118 + 125
243 = 243
Hence : Values are same.
Verified : a - (- b) = a + b
Similar questions